"If I'm sailing with a girl, I get identified as a 'marshmallow' ": Gendered practices of school sport sailing in Western France and California. (February 2021) - Schmitt, Anne; Atencio, Matthew; Sempé, Gaëlle
Gendered divisions and representations can be especially problematic issues underpinning participation in water-based lifestyle and sporting activities. Sailing has particularly been found to be dominated by male participants who tend to dictate everyday codes of practice and symbolic representation. Female sailors are therefore regularly portrayed as inauthentic members of this activity and their participation also typically reflects much lower rates than males. In this paper, we develop these critical ideas about gendered sailing in the context of an 18 months comparative qualitative study involving 24 interviews and 113 hours of ethnographic field observations with five coaches, three physical education teachers, and 16 sailors. This study examined school sailing programmes in Western France and California in terms of the gendered practices and relationships that developed amongst young sailors and supporting adults. Bourdieu's theory of embodied power reproduction and masculine domination is used to analyse how school sport sailing programmes often benefited male participants. Within both Western French and Californian sailing contexts, young men were viewed as being more legitimate participants and regularly took up the lead role of skipper – young women were considered secondary participants and were typically positioned as crew members. Notions of embodied agency are subsequently developed to illustrate how young women sometimes contested the male-dominated gender order found within Franco-American school-based sailing programmes.